How life style has been evaluated: a systematic review - Pôrto, Elias Ferreira; Kümpel, Claudia; Castro, Antônio Adolfo Mattos de; Oliveira, Isis Modesto de; Alfieri, Fábio Marcon (Acta Fisiátrica, 2015)
The term lifestyle corresponds to the set of habits and customs that can be influenced and modified and which can contribute to promoting health. Objective: This study was to make a systematic review on the subject of lifestyle, what methods have been used to evaluate lifestyle, and what is considered a healthy lifestyle. Method: This study consisted of a systematic review on the possible methods of evaluating the lifestyle and habits of what is considered healthy lifestyle. The survey was conducted in electronic databases, national and international, LILACS, MEDLINE, PubMed, and SciELO, and free search on Google Brazil, by consulting the following descriptors: "life style" associated with "healthy. Results: We found 142 articles published between 1990 and 2012, 105 of which did not meet the established criteria, 28 were considered eligible and were included in the study, 10 used randomized and pseudo-randomized samples, and 17 were not randomized. Among the articles selected, there were four proposals to validate lifestyle-assessment instruments, and one systematic review. The instruments used were not very reliable for assessing lifestyle, and their methods were not responsive. Conclusion: These studies demonstrate the importance of a healthy lifestyle and that it be started early and continued throughout life; they define the main actions related to a healthy lifestyle as well as control of metabolic parameters, physical activities, and healthy eating, but the lifestyle-evaluation instruments are still poor in responsiveness.